Three‐Dimensionally Scaffolded Hydrogel@Sulfur Composite as a Binder‐Free Polysulfides‐Adsorptive Cathode for High‐Performance Lithium‐Sulfur Batteries. Issue 5 (12th April 2019) - Liu, Jinyun; Zhou, Ping; Shen, Zihan; Zhang, Huigang; Jiang, Mingxi; Han, Yanqiang; Li, Jinjin; Li, Jianwei
Abstract : Chemically and mechanically robust sulfur (S) cathodes are highly significant for high‐performance lithium‐sulfur (Li‐S) batteries. Herein, a novel 3D hydrogel@S composite as binder‐free high‐performance cathode is presented, which consists of a 3D conductive hydrogel polyaniline (PAN) scaffold coated with dense S particles. The 3D PAN@S composite exhibits polysulfides‐adsorptive performance, suitable structure for accommodating the volume change of S upon lithiation, and improved overall conductivity of the electrode. After cycling for 100 times at 0.2 C, the binder‐free 3D PAN@S composite shows a capacity of 816 mAh g −1, along with a Coulombic efficiency as high as 99.9%. A good electrochemical performance is also achieved when cycling at a high temperature of 50 °C. In addition, the adsorptive effect of PAN towards polysulfides is demonstrated through density functional theory calculations on the adsorption energies. Abstract : A novel 3D scaffolded hydrogel@sulfur composite is presented as a binder‐free polysulfides‐adsorptive cathode for lithium‐sulfur batteries. Density functional theory calculations on surface energy demonstrate an efficiently adsorptive effect of the hydrogel towards polysulfides, which enables a high lithium storage performance of the battery.